Impact of Multidisciplinary Project Based Learning on Teacher Collaboration Skill - Utami, Epong; K Khaerudin; Murni Winarsih (Journal of Science and Education (JSE), 2025)
The digital era requires students to be able to improve their 21st century abilities. One approach that can be used is project-based learning. This ability improvement must also be supported by all teachers so that there is a need for teacher collaboration in carrying out project-based learning. This form of collaboration can be done by integrating each subject in accordance with the project theme to not only provide knowledge but also the mentoring process from the planning stage to the assessment at the project exhibition. To realize this, it is necessary to implement multidisciplinary project-based learning. The purpose of this study is to explore the impact of the application of multidisciplinary project-based learning on improving teachers' collaboration skills. This study uses a qualitative research method with 6 respondents of teachers who teach grades 7 and 8 at the School of Human Junior High School. The data collection used is by observation both before and after the implementation of multidisciplinary project-based learning. The results of the observation are then reflected qualitatively with the indicators of collaboration skills observed following Greenstein's (2012) theory, namely (1) actively participating; (2) work productively; (3) be re-sponsible; (4) flexibility and compromise; (5) mutual respect between group members. The results of this study show that there is an improvement in teachers' collaboration skills after the implementation of multidisciplinary project-based learning. 4 out of 5 indicators are categorized as very good and 1 indicator is categorized as good. Significant changes are found in the attitude of responsibility of each member towards the projects implemented.